Blackhorse riders : a desperate last stand, an extraordinary rescue mission, and the Vietnam battle America forgot - Keith, Phil. 1946- (St. Martin's Press, 2012)
Documents the daring March 1970 campaign by the Blackhorse Regiment to rescue an infantry unit that was surrounded and outnumbered by Northern Vietnamese forces, and describes the thirty-year effort to formally commend their bravery.